About the Place of Poetic Translation in Semio-sphere - Balesnij, Boris l. (Respectus Philologicus, 2003)
The present article defines a poetic text as a cultural semio-sphere phenomenon: it arises according to the laws of semio-sphere and its translation means the process of transition from semio-sphere of one culture to another. The specific semio-sphere of translation is also analyzed in the article. It has to belong equally to the semio-sphere of national culture of original language and to the semio-sphere of the target translation language culture, and at the same time it has not to belong to any of them entirely and be something special and valuable itself.
Keywords: semiotics; historical semiotics; translation theory; semiotic structure; semio-sphere